The relationship between perfectionism, anxiety, and putting performance: An investigation of the yips in golf - Chambers, T. P.; Marshall, D. V. J. (International Journal of Golf Science, 2017)
This study examined the effects of anxiety and perfectionism on putting performance and their relationship to the yips, a specific type of choking in golf. Two hundred and eighty amateur golfers completed an online questionnaire that included items on anxiety (Smith, Smoll, Cumming, & Grossbard, 2006), perfectionism (Stöber, Otto, & Stoll, 2004), and putting performance. Results indicated that 26.1% of the participants have experienced the putting yips when executing a putting stroke in golf. A series of hierarchical regression analyses revealed that participants who independently reported higher anxiety levels, and higher perfectionism reported significantly greater disruptions in putting performance. The best predictors of disrupted putting performance were anxiety and negative reactions to imperfection that together accounted for 35% of the explained variance. Anxiety also fully mediated the relationship between perfectionism and disruptions to putting performance. These findings add to the existing choking, and golfing literature, and are discussed in this context.